The Effect of Pressing Temperature and Time on the Quality of Particle Board Made from Jatropha Fruit Hulls Treated in Acidic Condition - Iswanto, Apri Heri; Febrianto, Fauzi; Hadi, Yusuf Sudo; Ruhendi, Surdiding; Hermawan, Dede (Makara Journal of Technology, 2013)
The high of pH of jatropha fruit hulls causes the negative properties of particleboard made from this material. Adjusting the particle acidity and pressing conditions (temperature and time) is among the technical modifications available to improve this particleboard’s properties. Particle acidity has been adjusted in a previous research project, and immersing the particles in acetic acid was found to be the best treatment in this preliminary research. In order to improve the particleboard’s properties, an experiment was conducted to determine the best pressing temperature and time. The objective of the research was to evaluate the influence of pressing temperature and time on the physical and mechanical properties of the board. Jatropha fruit hulls were immersed in 1% acetic acid solution for 24 hours. UF resin was used as the adhesive in the amount of 10%. The pressing temperatures and times used in this research were 110 °C, 120 °C, and 130 °C for 8 and 10 minutes, respectively. The particleboards were tested to determine their physical and mechanical properties according to JIS A 5908-2003. The result showed that pressing at 130 °C for 10 minutes resulted in the best physical and mechanical properties. Increasing the pressing temperature at a constant time or increasing the pressing time at a constant temperature caused the particleboard to exhibit decreased water absorption. The thickness swelling and modulus of elasticity (MOE) of the particleboard did not fulfil JIS A 5908-2003.